EXPERIMENT AND SIMULATION ON MECHANICAL PROPERTIES OF OSTEOPOROTIC MOUSE BONE (MT) - ZHAO Qing; YIN ZiYang; ZHOU Wen; REN GuanLin; KUANG ChunMei; HU Cong; ZHOU ChangJiang (Jixie qiangdu)
The osteoporosis model of mouse tibia was established based on castration, and the effect of osteoporosis on the mechanical properties of tibia was investigated. The two-dimensional sections of mouse tibia were obtained by Micro-CT. The three-dimensional digital model of mouse tibia was obtained by reconstruction technology, and trabecular bone shape and density were analyzed. The effect of osteoporosis on the mechanical properties of tibia was explored by testing and finite element simulation. The results showed that osteoporosis could damage the trabecular structure and decrease the mechanical properties of tibia. Compared with healthy tibia, the maximum load, bending stiffness and elastic modulus of tibia decreased by 20%, 30% and 25%, respectively, and the simulation results were in good agreement with the experiment. This study provides an important basis for the clinical diagnosis and treatment of osteoporosis.